2005
DOI: 10.1007/s11926-005-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors in psoriatic arthritis

Abstract: The genetic factors that are associated with psoriatic arthritis (PsA) are intricately linked with those that predispose to psoriasis itself. The strongest association is with human leukocyte antigen-Cw*0602, although true susceptibility may lie with one of the neighboring genes along a disease-associated haplotype. There are a number of interesting candidate genes within the major histocompatibility complex (MHC) region with strong functional relevance that have been investigated in PsA. In addition, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…This is evidenced by family studies that show a genetic predisposition for psoriasis and PsA that is actually larger than that for a number of other autoimmune conditions. A number of studies have demonstrated that genes play an important role in the etiology of PsA [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by family studies that show a genetic predisposition for psoriasis and PsA that is actually larger than that for a number of other autoimmune conditions. A number of studies have demonstrated that genes play an important role in the etiology of PsA [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…MICA has two main forms of polymorphism: a “GCT” triplet repeat in the transmembrane region and a large number of single nucleotide polymorphisms (SNPs) in the part of the gene that encodes the extracellular binding domains. [2728] Some studies have found an association between PsA and the MICA-A9 (MICA allele which has nine GCT repeats), but relatively small numbers of patients have been studied considering the complexity of the condition. In a Spanish population, the trinucleotide repeat polymorphism MICA-A9 corresponding to the MICA-002 allele was associated with PsA (but not psoriasis), independent of HLA Cw * 0602.…”
Section: Genes Within the Mhc Regionmentioning
confidence: 99%
“…[21] TNF-α is a key inflammatory cytokine in psoriasis and PsA and is found in high levels in the serum, synovial fluid, and synovial membrane of patients with PsA. [27] Associations have been reported between the TNF-α–308 polymorphism in the promoter region of the TNF-α gene and PsA. [34] The TNFα–308 polymorphism has been associated with the presence of joint erosions, progression of joint damage, and early age of the onset of PsA.…”
Section: Genes Within the Mhc Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA B27 ve HLA CW6 birlikteliği sıktır. Kırk yaşından sonra başlayan geç başlangıçlı tip psoriasiste genellikle deri lezyonları ile birlikte veya daha önce artrit meydana gelir, ailesel öykü yoktur, HLA DR7 ve HLA DR3 birlikteliği sıktır 1,5,[6][7][8][9] . HLA B27, 6.…”
Section: Introductionunclassified